2005
DOI: 10.1017/s0267190505000061
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategy Instruction: Current Issues and Research

Abstract: This chapter begins with definitions and an overview of methods used to identify learners' strategies, then summarizes what we have learned from the large number of descriptive studies of strategies reported by language learners. Research on language learning strategies has a history of only about thirty years, and much of this history has been sporadic. The 1980s and early 1990s were a period of substantial research on language learning strategies, much of it descriptive. This period was followed by an appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
345
0
20

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(418 citation statements)
references
References 40 publications
6
345
0
20
Order By: Relevance
“…Magogwe & Oliver, 2007;Oxford, 1990;Sheorey, 1999). One possible explanation for the different findings found in the studies mentioned above and many others might be related to the context of learning situation, which could have a strong influence on learners" choice of language learning strategies (Chamot, 2005;Cohen, 1998;Zhang, 2008). Some studies argue that the strategies frequently used by proficient language learners in an Asian FL (foreign language) context differ drastically from those in the North American SL (second language) context (Gu, 1996;LoCastro, 1994;Takeuchi et al, 1999;Takeuchi & Wakamoto, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Magogwe & Oliver, 2007;Oxford, 1990;Sheorey, 1999). One possible explanation for the different findings found in the studies mentioned above and many others might be related to the context of learning situation, which could have a strong influence on learners" choice of language learning strategies (Chamot, 2005;Cohen, 1998;Zhang, 2008). Some studies argue that the strategies frequently used by proficient language learners in an Asian FL (foreign language) context differ drastically from those in the North American SL (second language) context (Gu, 1996;LoCastro, 1994;Takeuchi et al, 1999;Takeuchi & Wakamoto, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…The second strand of research in Figure 1 corresponds to research on writing strategy instruction, an area of research conspicuously almost absent from Chamot's (2005) review of language learning strategy instruction. What is more, in his meta-analysis of strategy instruction research, Plonsky (2011) noted an imbalance in the attention paid to the four language skills in strategy instruction research and concluded that "further research [is] needed on the effects of SI on writing" (Plonsky, 2011(Plonsky, , p. 1017.…”
Section: Strand 2: Strategy Instruction Studiesmentioning
confidence: 99%
“…However, the field of strategies has also faced criticism and debate (Rees-Miller, 1993;Dörnyei & Skehan, 2003;Dörnyei, 2005;Macaro, 2006Macaro, , 2007Macaro, , 2010Manchón, 2008) concerning issues such as lack of agreement in definition and categorization of strategies, lack of a theoretical framework, the teachability of strategies or different approaches to research methodology and data analysis (Dmitrenko, 2017). All in all, despite the criticism, the field of strategy research is very much alive as the publications of current status of research (Chamot 2005(Chamot , 2011Griffiths, 2013;Hu, 2016) and the 2014 publication of a special issue in the international journal of Applied Linguistics, 'System', demonstrate.…”
Section: Reading Strategy Instruction Researchmentioning
confidence: 99%